Studying the post-fire performance of tussock grasses in Patagonia: Survival, biomass production and early competition - Gittins Lopez, Cecilia Gabriela; Ghermandi, Luciana; Bran, Donaldo Eduardo (Elsevier, 2024)
Patagonia grasslands are subjected to two main disturbances, fire and grazing, but little information is available about its effects on vegetation. We studied post-fire survival and resprouting ability of two dominant grass species, Stipa speciosa and Festuca pallescens, for four years; evaluated the effect of early post-fire defoliation on both species; and tested whether competition is important in post-fire recovery in San Ramón Ranch, NW Patagonia (Argentina). To simulate grazing, a clipping treatment was applied at the beginning and end of growing seasons. Survival rates were high (>60%) and, after three years, biomass of both species in the burned area was similar to the unburned area. Competition seems to play an important role in the early post-fire recovery of both species, particularly in the case of F. pallescens that increased 87% the biomass production without competition. Fire may improve forage quality by eliminating the standing dead material, but early post-fire grazing might endanger the persistence of F. pallescens. We suggest requiring a resting period before livestock introduction and controlling grazing intensity.